HUBUNGAN PENGETAHUAN, FATALISME KANKER DAN KESADARAN WANITA USIA SUBUR (WUS) DALAM PENAPISAN TES IVA - Suryandari, Artathi Eka (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2014)
ABSTRAK    Death of cervical cancer can be prevented by doing an early  detection and the only cost-effective way is screening test of Visual Inspection with Acetic Acid (IVA). The purpose of  this study was to analyze the correlation of  knowledge,  cancer fatalism, level of awareness and the participation of Reproductive Aged Women (RAW) in IVA.  The research sample consist of 224 RAW as cases and controls in Purwokerto Timur using proportional random sampling techniques. The measurement of cancer fatalism using Powe Fatalism  Inventory and the level of awareness measured by the Self Regulation Questionnair. The analysis result was conducted by  chi-square and logistic regression. The analysis showed that the correlate factors of RAW?s participation in IVA was cancer fatalism (p=0.024) with OR 2.305 and level  of awareness (p=0.009) with OR 2.806, while the level of awareness was the most dominant  factor. It is concluded that in order to increase RAW?s participation in IVA is needed to increase the RAW?s awareness toward the benefits of screening test of IVA and fatal consequences of cervical cancer and to decrease cancer fatalism by providing the right knowledge about cervical cancer through religious sermons that are often followed by  RAW.   Key words: knowledge, fatalism, awareness,IVA  Kesmasindo, Volume 6(3) Januari 2014, Hal. 208-222